Dilution Ratio and Particle Loss Performance of a Newly Developed Ejector Porous Tube Diluter Compared to a Commercial Diluter - Dongho Shin; Hyunsoo Seo; Kee-Jung Hong; Hak-Joon Kim; Yong-Jin Kim; Bangwoo Han; Ga-Young Lee; Sung-Nam Chun; Jungho Hwang (Aerosol and Air Quality Research)
Abstract In this study, a new ejector-porous tube diluter was developed to accurately in situ measure particulate matter at the source, e.g., emissions at coal-fired power plants, and its dilution ratio and particle loss were compared to those of a commercial model. Whereas commercial models supply air to the porous tube diluter (PRD) using a high-pressure compressor, our device replaces the latter with a ring blower, thereby decreasing the power consumption for the same airflow rate. As a demonstration, particle size volume distributions of fly ash at a coal-fired power plant stack were determined for different dilution ratios. PRD flow rates of 10 and 20 L min−1 for the commercial diluter produced ~2-µm particle volume concentrations of 382 and 572 µm3 cm−3, respectively, from an initial (undiluted) volume concentration of 756 µm3 cm−3. However, PRD flow rates of 10 and 30 L min−1 for the developed device produced ~2-µm particle volume concentrations of 506 and 500 µm3 cm−3, respectively, from an initial volume concentration of 532 µm3 cm−3. These particle loss rates were confirmed through field testing.